Effects of Green HRM Practices on Employee Workplace Green Behavior: The Role of Psychological Green Climate and Employee Green Values - Dumont, Jenny; Shen, Jie; Deng, Xin (Human Resource Management, 2017)
AbstractAs an emerging concept, green human resource management (green HRM) has been conceptualized to influence employee workplace green behavior. This research empirically tested this link. We first developed measures for green HRM, and then drew on the behavioral HRM and psychological climate literature along with the supplies‐values fit theory, to test a conceptual model integrating the effects of psychological green climate and individual green values. Results revealed that green HRM both directly and indirectly influenced in‐role green behavior, but only indirectly influenced extra‐role green behavior, through the mediation of psychological green climate. Individual green values moderated the effect of psychological green climate on extra‐role green behavior, but it did not moderate the effect of either green HRM or psychological green climate on in‐role green behavior. These findings indicate that green HRM affects both employee in‐role and extra‐role workplace green behavior; however, this occurs through different social and psychological processes. © 2016 Wiley Periodicals, Inc.